The Role of Service Quality and Human Resource Quality on Student Satisfaction in Education: Organizational Commitment as an Intervening Variable - Setyowati, Ely; Suyoto, Suyoto; Soelistya, Djoko (Budapest International Research and Critics University, 2022)
Higher education is present as a forum that has a considerable contribution in improving the quality of human resources in a nation according to the Law of the Republic of Indonesia Number 12 of 2012 concerning Higher Education point c reads; that in order to increase the nation's competitiveness in facing globalization in all fields, higher education is needed that is able to develop science and technology and produce intellectuals, scientists, and/or professionals who are cultured and creative, tolerant, democratic, have strong character, and dare to defend the truth for the interests of the nation. Universities as organizations that aim at service satisfaction are currently no longer reliable in terms of competitive advantage in this era of very high competition because other universities are also doing the same thing, so organizations need to emphasize commitment to achieving organizational goals by proactively improving the organization's image and increase student loyalty by looking at the quality of service and the quality of human resources (HR). The research method used is a quantitative approach with a total of 369 respondents with data analysis used through the SmartPLS 3.0 program, while the results obtained in this study are (1) Service Quality on Student Satisfaction has a direct but not significant effect; (2) Service Quality has a direct and significant effect on Organizational Commitment; (3) Quality of Human Resources has a direct but not significant effect on Organizational Commitment; (4) the quality of human resources has a direct and significant effect on student satisfaction; (5) Organizational Commitment has a direct and significant effect on Student Satisfaction; while (6) the quality of service has not been able to directly increase student satisfaction, and Organizational Commitment as a very important mediation needed to be able to increase the influence of Service Quality on student satisfaction; and (7) the quality of human resources can directly increase student satisfaction even without going through organizational commitment, so that the existence of organizational commitment as a mediation is not needed to be able to increase the influence of service quality on student satisfaction